Genetic instability and diminished differentiation capacity in long-term cultured mouse neurosphere cells - Vukicevic, Vladimir; Jauch, Anna; Dinger, Timo C.; Gebauer, Linda; Hornich, Veronika; Bornstein, Stefan R.; Ehrhart-Bornstein, Monika; Müller, Albrecht M. (Mechanisms of ageing and development, 2010)
The potential use of neural stem cells in basic research, drug testing and for development of therapeutic strategies requires large scale in vitro amplification, increasing the probability of genetic instability and transformation. Little is known, however, about potential correlations between long-term culture of neural stem and progenitor cells (NSPCs), changed differentiation and self-renewal capacities, and the occurrence of chromosomal instability. This study investigates the effect of extended culture time on self-renewal, differentiation capacity, cell cycle phase distribution, telomere length, telomerase activity and chromosomal stability on fetal brain-derived cells that form floating sphere colonies (neurospheres)...
Gesehen am 19.09.2023